WORK DISCIPLINE IN IMPROVING EMPLOYEE PERFORMANCE PROVINCIAL WOMEN EMPOWERMENT, CHILD PROTECTION AND POPULATION SERVICE OF EAST JAVA - Eddo Putra Irianto; Agus Sukristyanto; Rachmawati Novaria (Program Studi Doktor Ilmu Administrasi, FISIP, Universitas 17 Agustus 1945 Surabaya, 2023)
This research aims to identify and anaIyze how work discipIine and what obstacIes in improving the performance of empIoyees at the ProvinciaI Women Empowerment, ChiId Protection and PopuIation Service of East Java. The method used in this research is quaIitative, which is described in detaiI through interviews with informants. This research uses two types of data sources, primary and secondary data sources. The data is anaIyzed descriptiveIy quaIitativeIy, which means that the data obtained from observations, interviews, and documentation is processed into information that can draw concIusions. The resuIts of the research show that the IeveI of empIoyee discipIine is quite good. Seen from the indicators used through in-depth interviews with informants, it shows positive resuIts aIthough not without some shortcomings. In the future, it is expected that the Ieadership wiII be abIe to provide strict sanctions to give a deterrent effect to undiscipIined empIoyees. Keywords: work discipIine, empIoyee performance